2019
DOI: 10.1016/j.apsusc.2018.10.213
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing embedded ultra-small Pt nanoparticles as charge trapping layer in flashristor memory cells

Abstract: In this study, a methodology for producing highly controlled and uniformly dispersed metal nanoparticles were developed by atomic layer deposition (ALD) technique. All-ALD grown thin film flash memory (TFFM) cells and their applications were demonstrated with ultra-small platinum nanoparticles (Pt-NPs) as charge trapping layer and control tunnel oxide layer. The ultra-small Pt-NPs possessed sizes ranging from 2.3 to 2.6 nm and particle densities of about 2.5 × 10 13 cm -b . The effect of Pt-NPs embedded on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition to the effect of the substrate, the specific precursor material chosen may also impact the ALD process . In many sources, trimethyl­(methylcyclopentadienyl) platinum­(IV) (MeCpPtMe 3 ) is the traditional precursor material for Pt ALD. However, other literature sources have examined utilizing other Pt precursor materials such as platinum acetylacetonate . For this, it is important to account for the thermal stability of the precursor to obtain the desired result.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the effect of the substrate, the specific precursor material chosen may also impact the ALD process . In many sources, trimethyl­(methylcyclopentadienyl) platinum­(IV) (MeCpPtMe 3 ) is the traditional precursor material for Pt ALD. However, other literature sources have examined utilizing other Pt precursor materials such as platinum acetylacetonate . For this, it is important to account for the thermal stability of the precursor to obtain the desired result.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…Traditional ALD uses oxygen gas to react with the organic ligand of the precursor material to leave the desired material on the substrate. ,,, However, the use of oxygen typically requires a minimum operating temperature of 250 °C. Other researchers have used ozone as the reactant gas. ,,,,, The reactivity of ozone allows for the ALD process temperature to be reduced to around 100 °C while also functionalizing the surface of the substrate to improve nucleation . This allows for an increase in the growth rate when using ozone.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Recently, Orak et al have demonstrated the use of ALD for the successful deposition of ultrasmall Pt NPs, as a charge trapping layer in thin-film flash memory devices. 11 It is well known that the sensing ability of SMOs can be greatly enhanced by noble-metal doping. Pt-doped In 2 O 3 is one of the most interesting candidates among noble-metaldoped SMOs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among nanocrystal materials, metal NPs are considered highly promising because of a better lateral isolation of each storage site and high density of states . For charge storage in NVM devices, NPs such as Pt, Ag, and Au, embedded in dielectric layers, have been used, out of which Pt has been explored extensively. In a metal-based single-electron transistor, the metal NPs are separated from the gate material by a thin layer of dielectric . In order to accomplish better device performance, an adequate fabrication method, which can precisely control the NPs’ size and surface areal density, as well as the dielectric thickness, is highly important.…”
Section: Introductionmentioning
confidence: 99%